Pengaruh Enterprise Risk Management Disclosure dan Intellectual Capital Disclosure Terhadap Nilai Perusahaan - Abpriendi Mz, Abdi; Soekardan, Dadan (Jurnal Riset Ekonomi dan Bisnis Mahasiswa : Brainy, 2025)
This study investigates the impact of Enterprise Risk Management Disclosure (ERMD) and Intellectual Capital Disclosure (ICD) on Firm Value in property sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Utilizing a quantitative method with a purposive sampling technique, 39 companies were selected from a total population of 94. Data were analyzed through classical assumption tests, simple linear regression, and hypothesis testing (t-test) using secondary data from official annual reports. The results demonstrate that both ERMD and ICD have a significant positive effect on Firm Value, with contributions of 39.94% and 51.98%, respectively. These findings highlight that transparency in risk management and the disclosure of intangible assets are critical drivers in enhancing investor perception and corporate valuation, particularly amid the market fluctuations of the 2020–2024 period.